Do antibiotic-impregnated external ventriculostomy catheters have a low infection rate in clinical practice? A retrospective cohort study. (2nd January 2016) - Shekhar, H.; Kalsi, P.; Dambatta, S.; Strachan, R.
Abstract: Objective : External ventriculostomy-related infection (VRI) of cerebrospinal fluid (CSF) is a source of significant morbidity and mortality. In previous trials, antibiotic-impregnated ventricular catheters have been associated with lower incidence of CSF infections. We undertook this retrospective observational study to evaluate whether the introduction of antibiotic-impregnated external ventricular drains (EVDs) in 2004 has decreased VRI in our neurosurgical unit. Method : One hundred and fifteen patients underwent insertion of EVDs from January 2000 to March 2008. Data were collected for 99 patients with a total of 146 EVD insertions. The parameters studied were age, gender, ASA score, seniority of the surgeon, significant medical history, presence of trauma, concurrent surgeries, revisional surgery, use of peri-operative systemic antibiotic, use of antibiotic-impregnated external ventricular catheter, tunnelling of the catheter, duration of drainage and VRIs. Results : Eleven patients developed new VRI (12%). Analysis comparing infection incidence for various co-morbidities shows that systemic sepsis was associated with higher infection rates ( p  = 0.037). Revisional surgery ( p  = 0.036) and longer duration of catheterization ( p  = 0.001) were also found to be associated with VRI. The Standard catheters and the antibiotic-impregnated catheters had similar infection rates. The antibiotic-impregnated catheters tended to be infection-free for longer but these differences were not statistically significant. The duration of catheterization was significantly higher for the antibiotic-impregnated catheter group. In both groups, the majority of infections were caused by Gram-positive bacteria. Conclusion : Our study demonstrates that there was no statistically significant difference in the infection rates for the Standard and antibiotic-impregnated external ventriculostomy catheters. The duration of catheterization was significantly higher for the Antibiotic-impregnated catheter group. The antibiotic-impregnated catheter infections tended to occur later as compared with the Standard catheter group.